Leaf phenotypic plasticity of four Eleutherococcus species growing in the urban environment - Olena Vasheka; Viktoria Kryshenyk; Roman Palagecha; Nadiya Dzhurenko (Біологічні студії)
Background. Urban greening initiatives can significantly mitigate the challenges of climate change and urbanization. One of the innovative urban greening approaches involves the utilization of diverse tree and shrub varieties for urban landscaping. Species of Eleutherococcus, due to their exotic habitus and shade tolerance, stand out as attractive ornamental plants. It was previously demonstrated that adaptation of plants to a new environment is associated with phenotypic plasticity. The study aimed to establish the level of phenotypic plasticity for four Eleutherococcus species (E. lasiogyne, E. senticosus, E. sessiliflorus, E. trifoliatus) in an urbanized environment of Kyiv (Ukraine). Materials and Methods. The indexes of phenotypic plasticity (PI) were established based on seven morphological and ten anatomical features of leaves developed in sun and shade conditions. Anatomical measurements were carried out and analyzed by light microscopy (Zeiss Axiocam MRc 5 digital camera, Carl Zeiss) using Axiovision AC software. The phenotypic plasticity index was calculated for each parameter and species. Student’s t-test, one-Way ANOVA, Tukey’s HSD post hoc test, and Principal component analysis (PCA) were performed, including all considered leaf morphological and anatomical variables, grouped per species. All statistical analyses were performed using R version 3.5.3 (R Core Team). Results. The leaf traits of four Eleutherococcus species generally correspond to those of deciduous mesophyte trees, with LMA (the leaf dry mass per unit leaf area) ranging from 31 to 47 g m-2. The species significantly differed from each other in the level of variability of morphological and anatomical parameters. Total PI rankings are as follows: E. senticosus (0.34) → E. lasiogyne (0,30) → E. sessiliflorus (0.22) → E. trifoliatus (0.20). Conclusion. Our results contribute new insights into the phenotypic plasticity of trees and shrubs under new ecological and climatic conditions. Eleutherococcus senticosus exhibited the highest phenotypic plasticity among all investigated species, suggesting a high adaptive potential. The assessment of phenotypic plasticity can be useful for evaluating the adaptation potential of woody plants in urban greening.